Sigma-1 Receptor-Modulated Neuroinflammation in Neurological Diseases - Jia, Jia; Cheng, Jian; Wang, Cheng; Zhen, Xuechu (Frontiers in Cellular Neuroscience, 2018)
A large body of evidences indicates that sigma-1 receptor is an important drug target for a number of neuropsychiatric disorders. Sigma-1 receptor is enriched in central nervous system. In addition to neurons, both cerebral microglia and astrocytes express sigma-1 receptor. Activation of sigma-1 receptor is known to elicit potent neuroprotective effect and promote neuronal survival via multiple mechanisms, including promoting mitochondrial functions, defending oxidative stress and regulating neuroimmnological functions. In this review, we focus on the emerging importance of sigma-1 receptors in regulating neuroinflammation and discuss the recent advances on the receptor-modulating neuroinflammation in the pathophysiology and therapy of neurodegenerative disorders.